High-resolution three-dimensional atomic microscopy via double electromagnetically induced transparency. (September 2021) - Wahab, Abdul
Abstract : We aim to present a new scheme for high-dimensional atomic microscopy via double electromagnetically induced transparency in a four-level tripod system. For atom–field interaction, we construct a spatially dependent field by superimposing three standing-wave fields (SWFs) in 3D-atom localization. We achieve a high precision and high spatial resolution of an atom localization by appropriately adjusting the system variables such as field intensities and phase shifts. We also see the impact of Doppler shift and show that it dramatically deteriorates the precision of spatial information on 3D-atom localization. We believe that our suggested scheme opens up a fascinating way to improve the atom localization that supplies some practical applications in atom nanolithography, and Bose–Einstein condensation.